2015
DOI: 10.12988/ams.2015.511
|View full text |Cite
|
Sign up to set email alerts
|

Coeffcient bounds and Fekete-Szego problem for a class of analytic functions defined by using a new differential operator

Abstract: In this paper we obtain coefficient bounds and Fekete-Szegö inequalities for a new subclass B n,b α,µ,λ,ω (ϕ) of analytic functions defined by a new differential operator. Some of our results generalize the related work of some authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Several interesting properties and characteristics of the Hurwitz-Lerch Zeta function Φ(z, s, a) can be found in [9], and the references stated there in (see also [20], [21,30]). Srivastava and Attiya [30] (also see [2,8,19]) introduced and investigated the linear operator:…”
Section: Introductionmentioning
confidence: 99%
“…Several interesting properties and characteristics of the Hurwitz-Lerch Zeta function Φ(z, s, a) can be found in [9], and the references stated there in (see also [20], [21,30]). Srivastava and Attiya [30] (also see [2,8,19]) introduced and investigated the linear operator:…”
Section: Introductionmentioning
confidence: 99%
“…The study of operators plays an important role in the Geometric Function Theory and its related fields. It is observed that this formalism brings an ease in further mathematical exploration and also helps to understand the geometric properties of such operators better (see, for example [2], [3], [7], [12] and [15]). Recently, Darus andİbrahim [8] introduced a differential operator…”
Section: Introductionmentioning
confidence: 99%
“…Its source was in the disproof by Fekete and Szegö of the 1933 guess of Littlewood and Paley that the coefficients of odd univalent functions are limited by unity (see [9], has since received great attention, especially in many subclasses of the family of univalent functions). For that reason Fekete-Szegö functional was studied by many authors and a some assessments were found in a many subclasses of normalized univalent functions (see [3], [8], [12], [13] and [16]).…”
Section: Introduction and Definitionsmentioning
confidence: 99%